Associations between pre-existing comorbidities and in-hospital cardiovascular events and mortality among COVID-19 patients in Bangladesh: a secondary analysis of a prospective cohort study - Tippawan Liabsuetrakul; Farzana Islam; Abdur Rahim; Abdul Wadud Chowdhury; Kazi Fayzus Salahin; Md. Robed Amin; Shahin Akter; Shamim Talukder; Quazi Monirul Islam (BMJ Open)
Objective To identify the associations of in-hospital cardiovascular events and mortality with pre-existing comorbidities and cardiovascular disease (CVD) risk factors among COVID-19 patients in Bangladesh without vaccine availability.Design A secondary analysis of a prospective multicountry study.Setting Three COVID-19-designated hospitals in Bangladesh.Participants Adult patients aged ≥18 years with PCR-positive COVID-19 admitted between 10 October 2020 and 31 July 2021 at participating hospitals.Outcome measures In-hospital cardiovascular events and mortality.Main exposures Pre-existing comorbidities and cardiovascular risk factors.Results In 897 COVID-19 patients, 18.7% developed cardiovascular events and 12.6% died. After adjusting for clinical information and treatment, patients with two comorbidities (excluding CVD risk factors) were significantly associated with cardiovascular events (adjusted (adj.) OR 2.47, 95% CI 1.24 to 4.90). Patients with a higher heart rate at admission (adj. OR 1.03, 95% CI 1.01 to 1.04) and those who were receiving intravenous fluids (adj. OR 2.13, 95% CI 1.23 to 3.70) or antibiotics (adj. OR 4.54, 95% CI 1.47 to 14.01) had significantly higher odds of cardiovascular events. The odds of cardiovascular events were lower in those receiving antiviral medications (adj. OR 0.31, 95% CI 0.18 to 0.53). There were no interactions between comorbidities and other covariates in the models. Comorbidities and cardiovascular risk factors were not significantly associated with 30-day mortality in the Cox regression models after adjusting with clinical information and treatment. The mortality within 30 days of admission was significantly higher in patients receiving corticosteroids (adj. HR 2.82, 95% CI 1.48 to 5.38) and lower in those receiving antiviral treatment (adj. HR 0.53, 95% CI 0.34 to 0.81). Those having cardiovascular events significantly increased mortality hazard.Conclusions Clinical factors and treatment affected in-hospital cardiovascular events, which subsequently increased the risk of mortality within 30 days for COVID-19 patients. COVID-19 patients regardless of CVD risk factors and comorbidities require close monitoring for cardiovascular events.